(untitled) (Delta Medical College Journal, 2022)
Background: Optic nerve sheath fenestration (ONSF) is commonly used in idiopathic intracranial hypertension (IIH) with visual deterioration and visual improvement is observed post operatively in these patients. Objective: Retrospective evaluation of MRI observations in IIH patients who underwent optic nerve sheath fenestration (ONSF) with postoperative visual improvement. Materials and method: Optic nerve sheath fenestration (ONSF) was done in twenty four (24) patients with IIH having severe visual impairment. Post operatively all patients improved in their visual functions. The recorded pre operative MRI (of brain and orbit) of patients were reviewed and evaluated retrospectively. Results: Total number of MRI studied was 24. Male female ratio was 1:11. Posterior globe flattening was found in all 24 (100%) cases. Other findings were horizontal tortuosity of optic nerve (92%), optic nerve head protrusion (87.5%), optic nerve sheath distension (87%), and vertical buckling (62.5%). Ventricular size was normal in 92% cases and slit ventricle was found only in 8% cases. On magnetic resonance venogram (MRV) one sided transverse sinus abnormality was found in 25% cases. There was empty sella in 79% cases, more marked in three cases. Conclusion: The MRI findings in IIH patients with positive post ONSF result are of variable degree and prevalence except posterior globe flattening which was found in all cases. Delta Med Col J. Jul 2020 8(1): 21-27